Value added food products incorporating Musa balbisiana- a key to nutrition security - Duarah, Radali; Sharma, Daisy; Sarma, Manash (Journal of Postharvest Technology, 2021)
Mindful eating has recently gained attention and people are more cautious than ever. Having the market flooded with various conventional food products with health hazardous chemicals and artificial flavours, people have started to opt for flavours as natural as possible. Banana is one of the most important fruit crops of India contributing 16% of the world total fruit production. Each and every part of banana a rich source of various bioactive compounds like total phenols, carotenoids, flavonoids etc. The Banana fruit is highly perishable and it is important to convert them to semi perishable value added food products by applying appropriate processing techniques to reduce the post-harvest losses. Various value added food products can be obtained by using banana. The aim of this review is to provide information about the food value of banana and value added food products developed from different parts of banana plant. As value addition of banana plays significant role in human nutrition, especially as a source of vitamins, minerals and dietary fiber, thus value addition of such fruits and vegetables by formulation of different value added products are an important source of nutritional security.